PERAN BUDAYA KERJA DALAM MEMEDIASI PERBAIKAN BERKELANJUTAN DAN INOVASI KERJA TERHADAP KINERJA KARYAWAN - Saiful Saiful; Jajang Badruzaman; Asep Yusup Hanapia (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Human resources are an important aspect of business management, through innovative approaches that can improve the economic, technological, social, cultural and corporate environment. The purpose of this study was to identify and analyze the role of work culture in mediating continuous improvement and work innovation on employee performance in the footwear industry at PT. Changshin Reksa Jaya. As well as the influence of continuous improvement and work innovation into a work culture in improving the performance of footwear industry employees. The research method used in this study is a survey method, while the types of data used in this study are primary data and secondary data. The object of this research is the footwear industry employees of PT. Changshing Reksa Jaya, with a sampling technique using a simple random sampling method. The data analysis technique used is path analysis. The results of this test prove that partially and simultaneously the role of work culture in mediating continuous improvement and work innovation has a significant positive effect on the performance of employees in the footwear industry at PT. Changshijn Reksa Jaya. Keywords: Continuous Improvement, Innovation, Culture, Performance